Impact of Early Intervention with Triiodothyroacetic Acid on Peripheral and Neurodevelopmental Findings in a Boy with MCT8 Deficiency - Yağmur Ünsal; Gamze Hayran (Galenos Yayincilik, 2024)
Monocarboxylate transporter 8 (MCT8) deficiency is a rare genetic disorder characterized by peripheral thyrotoxicosis and severe cognitive and motor disability due to cerebral hypothyroidism. 3,3',5-triiodothyroacetic acid (Triac) was shown to improve peripheral thyrotoxicosis but data on neurodevelopmental outcome are scarce. We present a case of MCT8 deficiency and the experience with Triac focusing on change in neurodevelopmental and peripheral features. A five-month-old boy was referred because of feeding difficulty, central hypotonia and global developmental delay. Despite six months of physiotherapy, physical developmental milestones did not improve, and distal muscle tone was increased. A hemizygous pathogenic variant in SLC16A2 was found and MCT8 deficiency was confirmed at 19-months. Thyroid stimulating hormone was 2.83 mIU/mL, free thyroxine 6.24 pmol/L (N=12-22) and free triiodothyronine (FT3) 15.65pmol/L (N=3.1-6.8). He had tachycardia, blood pressure and transaminases were elevated. Triac was started at 21-months. Two weeks after treatment, FT3 dramatically decreased, steady normal serum FT3 was achieved at 28-months. Assessment of neurodevelopmental milestones and signs of hyperthyroidism were evaluated at baseline, 6 months and 12 months after treatment. Signs of hyperthyroidism were improved by 6 months. Developmental composite scores of Bayley Scales of Infant Developmental 3rd Edition remained the same but important developmental milestones (head control, recognition of caregiver, response to his name) were attained, regression in the attained milestones were not observed. Initial dose, management protocol for Triac and research into its efficacy on neurodevelopmental signs in MCT8 deficiency are progressing. This case presents evidence that Triac may resolve peripheral thyrotoxicosis successfully and may slow neurodevelopmental regression, while some developmental milestones were achieved after one year of treatment.